Sovereignty and International Criminal Law - Pérez Sánchez Cerro, José Luis (2020)
In this article I briefly develop the issues of sovereignty from the point of view of international law and how it is necessary to update the legislation of the countries, in accordance with its progress. Modern international law issues are essential for its application and validity and as a way to effectively incorporate into the lives of citizens, therefore must be introduced into the internal law of the countries. International law, especially the 21st century, has turn off new twist that introduces the individual, the human person, as an element of international criminal law, as a result of the processes that, intuitu personae, have been dealing with in the International Criminal Court.